The effect of prior exercise intensity on oxygen uptake kinetics during high-intensity running exercise in trained subjects - do Nascimento, P. C.; de Lucas, R. D.; de Souza, K. M.; de Aguiar, R. A.; Denadai, B. S.; Antonacci Guglielmo, L. G. (European Journal of Applied Physiology, 2015)
Purpose